Choroid plexus carcinoma: A case report and literature review - Chik, Azhani; Chan, Kin Hup; Mustafa, Fadhli; Awang, Mohamed Saufi (Open Access Text ( OAS), 2017)
Choroid plexus carcinoma is a rare tumor representing less than 1% of all brain tumors. In adult, the incidence is extremely rare making the diagnosis difficult. Majority of choroid plexus tumor is found in the ventricle. However, ectopic sites such as intracranial extraventricular or spine have been reported. We report a case of choroid plexus carcinoma in a 39-year-old man. The clinical presentation, pathology and management are discussed.